Application of a salt substitute in bitter taste suppression and toward better acceptance of cruciferous vegetables in diet - Gajari, Davorka; Rumbak, Ivana; Ranilović, Jasmina; Tomić-Obrdalj, Helena (Appetite, 2022)
The addition of table salt has been reported to enable better acceptance when consuming the least preferred vegetables belonging to the Cruciferae family. Considering the adverse effect of excessive table salt intake on incidence of hypertension and cardiovascular diseases, it is essential to explore an alternative healthier option for better acceptance and to encourage consumption of these vegetables. In this study, 261 adult participants were evaluated for their preferences toward basic tastes and food as well as sensory evaluation of a meal prepared from cruciferous vegetables with the addition of two different salts, sodium chloride and salt substitute containing a blend of potassium and sodium salts. A general questionnaire was used to assess taste and food preferences, while the Cruciferous Vegetable Food Frequency Questionnaire (CVFFQ) was used for vegetable intake assessment. The Labeled Magnitude Scale (LMS), Just About Right (JAR) scale, and several hedonic scales were used to determine taster status and sensory evaluation. The results show that a low concentration of the salt substitute did not impact bitterness suppression but did result in higher preference of the cruciferous vegetable meal. Although, subjects self-reported to have salty taste preferences were more sensitive to bitter taste, they did not perceive samples as less salty and less acceptable than subjects with lower sensitivity. The results show the necessity for further examination of the effectiveness of different concentrations of the assessed salt substitute in suppressing perceived bitterness of cruciferous vegetables and regarding their overall acceptance for inclusion in diets.